Penggunaan Gaya Bahasa Indonesia Dalam Film Habibie Dan Ainun 2012 - Eva Nurmala; Nabila Islamia Nazla Hambali (Pusat riset dan Inovasi Nasional, 2023)
This article aims to describe the film Habibie & Ainun, an Indonesian biographical drama film which was released on December 20, 2012. This film stars Reza Rahardian and Bunga Citra Lestari. This film is based on the memoir of the same name, which was written by Habibie about his life story with his late wife, Hasri Ainun Habibie. In this film we analyze the use of language style. Language style is the use of figurative words and appropriate comparisons to express feelings and thoughts with a specific purpose. The use of a foreign language in the main character is an obstacle to the effectiveness of the Indonesian style. The method of analyzing this film is descriptive qualitative. With data collection techniques used are documentation techniques, observe and record. Based on the results of the analysis, it was found that a variety of language styles showed comparative language styles, contradictory language styles, satire language styles, affirmative or repetition language styles.